Factors associated with spontaneous adverse drug reaction reporting among healthcare professionals in Vietnam. (5th September 2019) - Le, Thu Thuy; Nguyen, Thi Thanh Huong; Nguyen, Chi; Tran, Ngan Ha; Tran, Lan Anh; Nguyen, Thanh Binh; Nguyen, Nhung; Nguyen, Hoang Anh
Abstract: What is known and objective: Under‐reporting is a major drawback of a voluntary adverse drug reaction reporting system in pharmacovigilance. However, little is known about facilitators and barriers to ADR reporting by healthcare professionals (HCPs) in developing countries. To investigate factors associated with adverse drug reaction (ADR) reporting among HCPs in Vietnam. Methods: A cross‐sectional survey of 2091 HCPs was conducted in 2015 at 10 hospitals throughout Vietnam. The binary outcome was ever reporting ADRs. Healthcare professionals knowledge, attitude and practice about ADR reporting were measured. Multiple logistic regression analyses examined factors significantly associated with ever ADR reporting. Results: Overall, 29.3%, 2.2% and 68.4% of the sample were doctors, pharmacists and nurses, respectively. More than half (59.3%) had ever reported any ADR. Facilitators for ADR reporting were educational training (OR = 1.77, 95%CI = 1.42‐2.22) and having better knowledge, such as awareness of ADR reporting regulation (OR = 1.63, 95%CI = 1.19‐2.21), of reporting time (OR = 1.76, 95%CI = 1.35‐2.29) and of necessary information in reporting form (OR = 1.94, 95%CI = 1.53‐2.45).Conversely, barriers to non‐reporting were unknown of reporting procedure (OR = 0.27, 95%CI = 0.22‐0.35), unavailability of reporting form (OR = 0.54, 95%CI = 0.42‐0.68) and lack of time (OR = 0.59, 95%CI = 0.46‐0.74). What is new and conclusion: Given the low ADR reporting rate among HCPs, educational interventions to improve their knowledge and attitude should be prioritized in Vietnam. Additional interventions addressing obstacles (i.e. availability and complexity of reporting form, lack of time) should be considered to improve both the quantity and quality of ADR reporting. Abstract : This study is among the first to reveal a substantial proportion (41%) of adverse drug reaction underreporting by healthcare professionals in Vietnam. Facilitators for adverse drug reaction reporting were better knowledge, while barriers were unawareness of reporting forms, and lack of time. Educational interventions are needed to increase both quantity and quality of adverse drug reaction reports among healthcare professionals.